Técnicas de comunicación asertiva para una educación parento-filial en sexualidad en los estudiantes de quinto grado, escuela Dr. Luis Felipe Zapater, Loja. 2016-2017. - Tatiana Johanna, Medina Tene (2017)
The present research is about Assertive Communication Techniques to an Education parentofilial, in the students of 5th grade of education at “Dr. Luis Felipe Zapater school”, Loja 2016- 2017; with the following general objective; To implement assertive communication techniques for parental-filial education in sexuality in the fifth grade of the “Dr. Luis Felipe Zapater school, Loja 2016-2017, the methods used were: scientific, inductive, analytical-synthetic and statistical, the technique used was the Family Communication Assessment Scale (CA-M / CAP), which helped to know what type of communication Parents with their children. The population was made up of 153 students and 153 parents, and a sample of 21 students and 21 parents was worked. It was concluded that with the proposed alternative, the expected results were obtained since in the pre-test it was obtained as Open communication 29% as a high percentage and in the post-test 81% was obtained, and as for the open communication with the father in the pre-test, 19% was obtained as high communication and the post-test a 76 %, And it is also recommended that parents use the techniques of assertive communication to maintain an open communication with their children on issof sexuality and thus can educate them in a simpler way